Thermal adaptation in Xenorhabdus spp., bacterial symbionts of entomopathogenic nematodes, Steinernema spp - He, Hongjun, 1962- (1998)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1998. Biology Bibliography: leaves 126-135 Physiological mechanisms of adaptation to temperature were investigated in four strains of Xenorhabdus spp. that originated from various geographical areas: Xenorhabdus bovienii NF strain and Xenorhabdus bovienii Umea strain (boreal origin), Xenorhabdus nematophilus All strain (temperate origin) and Xenorhabdus sp. TX strain (subtropical origin). The criteria included the effect of temperature on growth, capacity to synthesize isozymes of metabolic enzymes and modify fatty acids, in addition, the TX strain (undescribed) and the NF strain (newly isolated) were characterized through physiological and biochemical tests and cellulose acetate electrophoresis was evaluated for use in the taxonomy of this category of bacteria. -- The isozymes of nine enzymes were separated by cellulose acetate electrophoresis and compared among the four bacterial strains. The results indicated that these strains could be distinguished from one another on the basis of isozyme patterns at 25°C. Four enzymes [fumarate hydratase (FUM), malate dehydrogenase (NAD) (MDH), malate dehydrogenase (NADP~) (ME), and phosphoglucomutase (PGM)] displayed species-specific isozyme patterns, and the isozyme patterns of arginine phosphokinase (APK) distinguished between the NF strain and the Umea strain. Additionally, the isozyme patterns in the NF and Umea strains were temporally stable for all enzymes, except ME (Umea strain) and IDH (NF strain). These findings suggested that cellulose acetate electrophoresis could be an important tool for the identification of Xenorhabdus species or even strains. -- Xenorhabdus sp. TX strain was physiologically and biochemically distinguishable from the five described Xenorhabdus species and from the related bacterium, Photorhabdus luminescens. The TX strain differed from any of the five described Xenorhabdus species or P. luminescens in at least one of the following characteristics: growth at 10°C (-), growth at 37 C (+), catalase (-), bioluminescence (-), absorption of bromothymoi blue dye (+), lipase (-), urease (-), phosphatase (-), alkaline phosphatase (w: weak), ribose acidification (-), glycerol acidification (+), salicin acidification (-), cefalothin resistance (-), amoxiliine & calvulanic acid resistance (-), and esculin hydrolysis (-). The NF and Umea strains displayed identical reactions for all the tests in this study, indicating that they were inseparable on the basis of common physiological and biochemical tests. -- Growth of the four Xenorhabdus strains was examined over a wide range of temperatures. The boreal strains (NF, Umea) grew at culture temperatures from 0°C to 32°C, the All strain from 10°C to 32°C, and the TX strain from 15°C to 38.5°C. The optimal temperature, based on growth rates, was 25°C for the two boreal strains, 30°C for the All strain and the TX strain. The boreal strains (NF, Umea) were categorized as psychrotrophs, and the All and TX strains as mesophiles. -- The effect of culture temperature on the isozymes of seven enzymes was studied in the four Xenorhabdus strains. All four strains displayed temperature-related variations in isozyme patterns. Five enzymes displayed temperature related modifications in isozyme banding patterns in the Umea strain, four in the NF strain, three in the All strain and two in the TX strain. These results indicated that these bacteria may physiologically adapt to temperature by altering the synthesis of isozymes. -- All four strains responded to low temperatures by increasing monounsaturated fatty acids (16:10,7 and 18:io,9) with concomitant decreases in the prominent saturated fatty acid (16:0), indicating that these bacteria could adapt to temperature by modifying the degree of fatty acid unsaturation. Other fatty acids (14:0, 17:0, 17:0C, 20:0), present in lower amounts, were affected by temperature in three strains (All, NF, Umea) while they did not significantly vary from 20°C to 35°C in the TX strain. This study suggested that cold adaptation in X bovienii may involve shifts in fatty acids composition induced by temperatures well above freezing.